P283 Decrease in bowel wall thickness at intestinal ultrasound accurately detects early endoscopic remission and improvement in ulcerative colitis patients on tofacitinib: a longitudinal prospective cohort study. (27th May 2021) - de Voogd, F; Van Wassenaer, E; Mookhoek, A; Bots, S; Van Gennep, S; Duijvestein, M; Ponsioen, C; Löwenberg, M; D'Haens, G; Gecse, K
Abstract: Background: To assess disease activity in ulcerative colitis (UC) intestinal ultrasound (IUS) highly correlates with endoscopic outcomes. However, data on treatment response evaluated with IUS is limited. In this study we aim to evaluate bowel wall thickness (BWT) at follow-up to determine treatment effectiveness in moderate-severe UC patients treated with tofacitinib according to central read endoscopy and histology. Methods: Patients with moderate-severe UC (endoscopic Mayo score (EMS)≥2) starting tofacitinib 10 mg bid were included. Disease activity was evaluated by recorded IUS cine-loops and video-taped endoscopies with biopsies from the sigmoid (SC) and descending colon (DC) at baseline and at 8 weeks. BWT and EMS were assessed per segment (SC and DC). Histology was scored for the SC with the Robarts Histology Index (RHI). BWT, EMS and RHI were centrally read and for IUS there was a second reader. Endoscopic remission (ERem) was defined as EMS=0, endoscopic improvement (EI) as EMS≤1 and endoscopic response (ERes) as a decrease of EMS≥1. For statistical analysis a Wilcoxon signed-rank and Spearman's test were used. Area under the ROC was used to determine optimal cut-off values. Inter-observer agreement was analyzed by intra-class correlation coefficient (ICC). Results: 29 patients were included and started tofacitinib. 10% reached complete ERem after 8 weeks, respectively. Per-segment analysis for EMS showed 22% and 53% reaching ER and 40% and 60% having EI in the SC and DC, respectively. BWT in SC and DC correlated highly with the EMS (rho=0.68, rho=0.75, both p<0.0001) and moderately with RHI (rho=0.49, p=0.002). Patients with EMS≥2 after 8 weeks had an increased BWT (SC: 4.32 ± 1.57 mm, DC: 4.38 ± 1.58 mm) when compared to ERem (SC: 2.10 ± 0.67 mm, DC: mean: 2.00 ± 1.18 mm, both p<0.0001) and EI (SC: 2.29 ± 0.76 mm, DC: 2.56 ± 1.38 mm, both p<0.0001) in the similar segment (Figure 1 and 2). BWT decreased after 8 weeks when there was ERes (SC: mean: -2.59 ± 1.44 mm, DC: -1.82 ± 1.01 mm, both p=0.007) and did not when there was no ERes (Figure 3). BWT cut-off values for ERem are reported in Figure 4. Furthermore, agreement for BWT in the SC and DC was excellent (ICC: 0.92 and ICC: 0.89), respectively. Conclusion: BWT reduction showed early endoscopic remission, improvement and response after 8 weeks of tofacitinib treatment and correlated with histology in this central read cohort. Furthermore, accurate and reliable cut-off values for BWT in SC and DC were found for endoscopic remission and improvement. Therefore, IUS should be incorporated in the standard follow-up and close monitoring of UC patients.